STAT6 gain-of-function disease: p.D519N is a new disease-causing variant that responds well to dupilumab treatment - Simran Samra, MSc; Eleanor Cook, MBBS; Jessica Wilson, APRN; Mehul Sharma, PhD; Liam Golding, MSc; David T. Yao, BSc; Rebecca A. Marsh, MD; Stuart E. Turvey, MBBS, DPhil (Journal of Allergy and Clinical Immunology: Global, 2025)
This case report presents a new genetic variant that causes STAT6 gain-of-function disease in 2 patients, expands the clinical phenotype of STAT6 gain-of-function disease, and describes its authors’ success in using therapeutics to manage this rare disease.